PENGARUH KONSUMSI SEDUHAN BUBUK BIJI KOPI TERHADAP KADAR GULA DARAH SEWAKTU PADA PENDERITA DIABETES MELLITUS TIPE 2 DI PUSKESMAS PIYUNGAN BANTUL - Agus Prasetyo; Sutanta (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2015)
Coffee was predicted able to increase insulin sensitivity, hampering glucose 6 phosphate hidrolisis in the lever and it is also hampering sugar absorption in the intestine so it can decrease blood glucose quality for the sufferer of diabetes mellitus type 2. This research aims to know the consumption influence of coffee seed powder toward at the time blood glucose quality for the sufferer of diabetes mellitus type 2 in Piyungan Public Health, Bantul. This research design was a pra-experimental with the design a one group pretest-postest design. The sample numbered 32 people who suffer a diabetes mellitus type 2 by using a purposive sampling technique. The respondent was asked to consumption the coffee three time a day for 14 days. The data analysis used a paired sample test. The research result shown an average deceasing of at the time blood glucose quality at the amount to 32 people as 42,96875 mg/dl. It is supported by the result of statistic test with pv = 0,000 < α = 0,05, mean while t count = 80,170 > t table = 2,039 which shown a differentiate the value of at the time blood quality significantly between before and after consuming coffee for the sufferer of diabetes mellitus type 2. Coffee can decrease at the time blood quality for the sufferer of diabetes mellitus type 2 with decreasing a means for the consumption coffee three time a day for 14 days.